New Small Nuclear RNA Gene-Like Transcriptional Units as Sources of Regulatory Transcripts - Pagano, Aldo; Castelnuovo, Manuele; Tortelli, Federico; Ferrari, Roberto; Dieci, Giorgio; Cancedda, Ranieri (PLOS Genetics, 2007)
By means of a computer search for upstream promoter elements (distal sequence element and proximal sequence element) typical of small nuclear RNA genes, we have identified in the human genome a number of previously unrecognized, putative transcription units whose predicted products are novel noncoding RNAs with homology to protein-coding genes. By elucidating the function of one of them, we provide evidence for the existence of a sense/antisense-based gene-regulation network where part of the polymerase III transcriptome could control its polymerase II counterpart.